2021
DOI: 10.1038/s41545-021-00099-1
|View full text |Cite
|
Sign up to set email alerts
|

Faecal pollution source tracking in the holy Bagmati River by portable 16S rRNA gene sequencing

Abstract: A suitcase laboratory was used for 16S rRNA amplicon sequencing to assess microbial water quality in the holy Bagmati River, Kathmandu, Nepal. SourceTracker analysis and Volcano plots revealed that microbial communities in the downstream part of the river were mainly contributed by untreated sewage. Seasonal variability in the sewage microbiome was reflected in the downstream river water quality. The bacterial genera Acidovorax, Geobacillus and Caulobacter predominated in the upstream sites, while genera conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…In Nepal, which has a monsoon climate, 16S rDNA of the Arcobacter spp. have been detected as major fecal bacteria in the Bagmati River during the monsoon season (Pantha et al 2021). Furthermore, it has been reported that the detection of A. butzleri by culture-based method increases during rainfall in Canadian rivers (Webb et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In Nepal, which has a monsoon climate, 16S rDNA of the Arcobacter spp. have been detected as major fecal bacteria in the Bagmati River during the monsoon season (Pantha et al 2021). Furthermore, it has been reported that the detection of A. butzleri by culture-based method increases during rainfall in Canadian rivers (Webb et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Min-ION applications comprised a wide range of sample types (Figure 3b), addressed a plethora of water research topics (Figure 3c), and included case studies from high, low, and upper middle-incomes, and least developed countries (Figure 3d). MinION applications were uneven in geographic distribution, and studies in the least developed countries were all from our own work [27,50,54,66,71]. However, the diversity of samples analyzed, the variety of remits, and notable applications in countries without universal access to safe water and sanitation support the utility of the MinION platform for water researchers.…”
Section: Trends In Minion Applications In Water Researchmentioning
confidence: 93%
“…Zooplanktonic biomass can be harvested with meshes having 200 µm openings [36], while the biomass of algae [74] and cyanobacteria [48] can be isolated by medium to large volume centrifugation (0.05 to 1 L). Most studies targeting bacteria and archaea filtered between 0.1 and 4 L of water through membranes with 0.22 µm pore size to capture the biomass [27,37,47,50,54,59,63,66,[68][69][70][71]73]. Filtration can take hours to complete [27], and sometimes water prefiltration through membranes with a pore size between 0.4 and 11 µm was used to remove suspended solids [37,76].…”
Section: Biomass Collection and Concentrationmentioning
confidence: 99%
“…Among other factors responsible for viral evolution, environmental factors play a major role in the emergence of new strains of pathogenic viruses [ 19 , 22 ]. New viruses keep emerging end re-emerging with time and changing environmental conditions and their detection has been possible using high-throughput sequencing [ 36 , 47 ]. There had been 10 major viral outbreaks in the past two decades, including regional and global outbreaks, as listed in Table 1 .…”
Section: Introductionmentioning
confidence: 99%